A new type of gene‐disruption cassette with a rescue gene for Pichia pastoris. (4th September 2017) - Shibui, Tatsuro; Hara, Hiroyoshi
Abstract : Pichia pastoris has been used for the production of many recombinant proteins, and many useful mutant strains have been created. However, the efficiency of mutant isolation by gene‐targeting is usually low and the procedure is difficult for those inexperienced in yeast genetics. In order to overcome these issues, we developed a new gene‐disruption system with a rescue gene using an inducible Cre/mutant–loxP system. With only short homology regions, the gene‐disruption cassette of the system replaces its target–gene locus containing a mutation with a compensatory rescue gene. As the cassette contains the AOX1 promoter‐driven Cre gene, when targeted strains are grown on media containing methanol, the DNA fragment, i.e., the marker, rescue and Cre genes, between the mutant‐loxP sequences in the cassette is excised, leaving only the remaining mutant‐loxP sequence in the genome, and consequently a target gene‐disrupted mutant can be isolated. The system was initially validated on ADE2 gene disruption, where the disruption can easily be detected by color‐change of the colonies. Then, the system was applied for knocking‐out URA3 and OCH1 genes, reported to be difficult to accomplish by conventional gene‐targeting methods. All three gene‐disruption cassettes with their rescue genes replaced their target genes, and the Cre/mutant–loxP system worked well to successfully isolate their knock‐out mutants. This study identified a new gene‐disruption system that could be used to effectively and strategically knock out genes of interest, especially whose deletion is detrimental to growth, without using special strains, e.g., deficient in nonhomologous end‐joining, in P. pastoris. © 2017 American Institute of Chemical Engineers Biotechnol. Prog., 33:1201–1208, 2017